Analisis Integrasi dan Segregasi Gen Ketahanan terhadap Hawar Daun pada Progeni F1 Hasil Persilangan Tanaman Kentang Transgenik dengan Non Transgenik - Alberta Dinar Ambarwati; Agus Purwito; Muhamad Herman; S. M. Sumaraow; Hajrial Aswidinnoor (Jurnal AgroBiogen, 2009)
Potato late blight, caused by Phytophthora infestans is one of the most devastating plant diseases. Potato yield losses due to this disease ranged from 47-100%. Frequent intervals and high rates of fungicide spray, currently practiced by potato growers to control the disease are expensive. Host resistance is an alternative control measure that is more economically and environmentally sustainable. Development of late blight resistant plants was conducted by crossing RB transgenic Katahdin SP904 andSP951 as male and two susceptible (Atlantic, Granola) varieties as female parents. F1 progenies were molecularly characterized for the integration of the RB transgene and evaluated for their segregations. Crossing data of Atlantic x transgenic Katahdin SP904 and SP951 produced 71 (57.72%)berries with average number of seeds per berry 139.58 and 83 (41.29%) berries with average number of seeds/berry 85.23, respectively. Granola x transgenic Katahdin SP904 and SP951 crosses gave higher results in terms of berry set (79.55 and 84.44%, respectively) than Atlantic x transgenic Katahdin crosses. A total of 554 F1 progenies were analyzed for thepresence of the RB PCR marker. An expected 619-bp and 840-bp band were amplified in the progenies that contain the RB gene. The RB gene was integrated in 65 (45.45%), 77 (47.83%), 47 (45.63%), and 71 (48.30%) F1 progenies of Atlantic x transgenic Katahdin SP904, Atlantic x transgenic Katahdin SP951, Granola x transgenic Katahdin SP904, andGranola x transgenic Katahdin SP951, respectively. Chisquare tests showed that all the four cross combinations followed a 1 : 1 segregation ratio.